2013
DOI: 10.1177/0300060513488510
|View full text |Cite
|
Sign up to set email alerts
|

Effect of smoke-free legislation on smoking cessation rates in teachers in Manisa, Turkey

Abstract: Objective: This study investigated the attitudes of Turkish adults towards the ban on smoking in public areas and compared annual smoking cessation rates before (pre-2009) and after (post-2009) the ban became law, using data from a survey of teachers. Methods: A self-reported questionnaire was used to collect data from teachers in Manisa, Turkey. Annual smoking rates were calculated. Joinpoint regression analysis was used to identify when a significant change occurred in the annual smoking cessation rate. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…However, there is a significant body of literature which demonstrates smoke-free legislation and policies result in smoking-related health improvements. International research has demonstrated smoke-free legislation and policies result in significant reductions in smoking rates [ 8 10 ]. A meta-analysis published in 2015 suggests smoke-free policies on university campuses specifically result in reductions in smoking rates of 14.7% after 1 year, and 8.3% after 3 years [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a significant body of literature which demonstrates smoke-free legislation and policies result in smoking-related health improvements. International research has demonstrated smoke-free legislation and policies result in significant reductions in smoking rates [ 8 10 ]. A meta-analysis published in 2015 suggests smoke-free policies on university campuses specifically result in reductions in smoking rates of 14.7% after 1 year, and 8.3% after 3 years [ 11 ].…”
Section: Introductionmentioning
confidence: 99%